Avian schistosome species in Danish freshwater lakes: relation to biotic and abiotic factors. (20th April 2021) - Al-Jubury, A.; Duan, Y.; Kania, P.W.; Tracz, E.S.; Bygum, A.; Jørgensen, L.v.G.; Horák, P.; Buchmann, K.
Abstract: Due to the increased prevalence of human infections with bird schistosome larvae (cercarial dermatitis) associated with bathing in Danish lakes, a nationwide survey of infected intermediate host snails was conducted in 2018–2020. Pulmonate snails (10, 225 specimens) were collected from 39 freshwater lakes (in the four major geographic regions in Denmark) and subjected to shedding. Released schistosome cercariae were isolated and identified by polymerase chain reaction and sequencing whereby Trichobilharzia regenti, Trichobilharzia franki, Trichobilharzia szidati and Trichobilharzia anseri were recorded. Infections were primarily determined by biotic factors such as the presence of final host birds and intermediate host snails and water temperature was noted as an important abiotic parameter associated with the infection. No clear connection with other abiotic factors (conductivity, alkalinity, pH, nitrogen, phosphorous) was seen. The widespread occurrence of infected snails, when compared to previous investigations, suggests that climate changes at northern latitudes could be responsible for the increased risk of contracting cercarial dermatitis.